Increased Detection of Cryptosporidium and Cyclospora spp. Oocysts in a Major Philippine Watershed Following Rainfall Events - MSMT, Frederick R. Masangkay RMT (Asian Journal of Biological and Life Sciences, 2019)
Waterborne Coccidians are emerging pathogens and are not entirely known in developing countries.CryptosporidiumandCyclosporahave been reported to cause diffuse watery diarrhea among immunocompetent and immunocompromised individuals alike but are not included in routine water quality examinations and medical diagnosis thereby leading to being underreported, undiagnosed or misdiagnosed and neglected as agents of intestinal-protozoan ailments. Water samples from a major watershed in Metro Manila, Philippines were investigated. A total of 99 samples (50-mL each), were filtered to obtain sediments that were processed and smeared onto glass slides and stained using modified Kinyoun’s acid-fast technique and microscopically observed forCryptosporidiumandCyclosporaoocysts. The 3-day collection (33 samples per day) returned positive results: Day 1 returned 42% (14/33) positive water samples, Day 2 with 85% (28/33) and Day 3 with 88% (29/33) forCryptosporidiumandCyclosporaoocysts. Overall, oocyst positivity was 72% (71/99). The results of this study support previous Coccidian findings in a major Philippine watershed and calls for further exploration of source water samples for intestinal protozoan pathogens, the identification of which can lead to initiatives in improving water quality assessment and the prevention of the transmission of waterborne protozoan pathogens to the general public.
Keywords: Coccidian; Cryptosporidium; Cyclospora; Philippines; Watershed